Heterogeneous political connections and stock price crash risk: evidence from the post-Najibnomics Malaysian economy - Tan, Kang Wan (2023)
This study investigates whether the behaviour of managers to suppress negative information from other shareholders is influenced by different types of political connections that a firm has. Specifically, this study examines whether the length of political connections and different types of political ties have a similar effect on stock price crash risk in normal times and times of political instability. Using Malaysia as a research setting, the results report evidence of heterogeneity in political connections with respect to the firm crash risk. Particularly, new politically connected firms and firms that establish political connections through politically connected directors have greater stock price crash risk. The results also highlight that the association between politically connected firms and crash risk is more profound during the political crisis. Additional analyses reveal that external monitors can only attenuate the crash risk in firms that are connected through politically connected board members, whereas the greater presence of independent directors on the board and audit committees cannot alleviate the crash risk for politically connected firms during periods of political instability. Overall, the managers conceal unfavourable news from other shareholders differs according to different types of political connections. This evidence informs the market participants about the relationship between heterogeneous political connections and stock price crash risk, reinforcing previous findings that crony capitalism, agency problems, weak governance, information opacity, and lower disclosure are well-entrenched in the emerging economy of Malaysia.